Junctional adhesion molecule-A is dispensable for myeloid cell recruitment and diversification in the tumor microenvironment - Kiss, Máté; Lebegge, Els; Murgaski, Aleksandar; Van Damme, Helena; Kancheva, Daliya; Brughmans, Jan; Scheyltjens, Isabelle; Talebi, Ali; Awad, Robin Maximilian; Elkrim, Yvon; Bardet, Pauline M. R.; Arnouk, Sana M.; et al. (Frontiers in Immunology, 2022)
Junctional adhesion molecule-A (JAM-A), expressed on the surface of myeloid cells, is required for extravasation at sites of inflammation and may also modulate myeloid cell activation. Infiltration of myeloid cells is a common feature of tumors that drives disease progression, but the function of JAM-A in this phenomenon and its impact on tumor-infiltrating myeloid cells is little understood. Here we show that systemic cancer-associated inflammation in mice enhanced JAM-A expression selectively on circulating monocytes in an IL1β-dependent manner. Using myeloid-specific JAM-A-deficient mice, we found that JAM-A was dispensable for recruitment of monocytes and other myeloid cells to tumors, in contrast to its reported role in inflammation. Single-cell RNA sequencing revealed that loss of JAM-A did not influence the transcriptional reprogramming of myeloid cells in the tumor microenvironment. Overall, our results support the notion that cancer-associated inflammation can modulate the phenotype of circulating immune cells, and we demonstrate that tumors can bypass the requirement of JAM-A for myeloid cell recruitment and reprogramming.